Metformin decreases the incidence of ovarian hyperstimulation syndrome: An experimental study - Elia, E.M. (2013)
Background: In assisted reproduction cycles, gonadotropins are administered to obtain a greater number of oocytes. A majority of patients do not have an adverse response; however, approximately 3-6% develop ovarian hyperstimulation syndrome (OHSS). Metformin reduces the risk of OHSS but little is known about the possible effects and mechanisms of action involved. Objective. To evaluate whether metformin attenuates some of the ovarian adverse effects caused by OHSS and to study the mechanisms involved. Material and methods. A rat OHSS model was used to investigate the effects of metformin administration. Ovarian histology and follicle counting were performed in ovarian sections stained with Masson trichrome. Vascular permeability was measured by the release of intravenously injected Evans Blue dye (EB). VEGF levels were measured by commercially immunosorbent assay kit. COX-2 protein expression was evaluated by western blot and NOS levels were analyses by immunohistochemistry. Results: Animals of the OHSS group showed similar physiopathology characteristics to the human syndrome: increased body weight, elevated progesterone and estradiol levels (P<0.001), increased number of corpora lutea (P<0.001), higher ovarian VEGF levels and vascular permeability (P<0.001 and P<0.01); and treatment with metformin prevented this effect (OHSS+M group; P<0.05). The vasoactive factors: COX-2 and NOS were increased in the ovaries of the OHSS group (P<0.05 and P<0.01) and metformin normalized their expression (P<0.05); suggesting that metformin has a role preventing the increased in vascular permeability caused by the syndrome. Conclusion: Metformin has a beneficial effect preventing OHSS by reducing the increase in: body weight, circulating progesterone and estradiol and vascular permeability. These effects of metformin are mediated by inhibiting the increased of the vasoactive molecules: VEGF, COX-2 and partially NOS. Molecules that are increased in OHSS and are responsible for a variety of the symptoms related to OHSS. © 2013 Elia et al.; licensee BioMed Central Ltd.